Rock characteristics of post-caldera volcanoes in Dieng volcanic complex (DVC), Central Java, Indonesia - Indranova Suhendro; Muhammad Nadafa Isnain; Rizky Wahyudi (UIR PRESS, 2022)
The Dieng volcanic complex (DVC) has one of the densest post-caldera volcanisms activity presents in Indonesia, yet its population density is considerably high. Therefore, it is important to identify the rock characteristics produced by the DVC post-caldera volcanoes to understand the risks and future hazards (i.e., eruption style). Based on lithology, we have classified DVC post-caldera volcanoes as (1) pyroclastic domain (PD; including Pagerkandang, Merdada, and Pangonan), and (2) lava domain (LD; including Prambanan, Kendil, Pakuwaja, Sikunir, Sikarim, and Seroja). PD is characterized by the domination of pyroclastic materials (mostly ash and lapilli) with oxidized scoria and volcanic lithics (fresh and/or altered) as the main components. The oxidized scoria clasts are moderately vesicular (27–41 % vesicularity; ) and phenocryst poor (<5 % phenocryst crystallinity, ), with plagioclase, pyroxene, and oxides as the main phenocryst phases. The LD is composed predominantly of lava. The observed lavas are typically dense (mostly <1 % , phenocryst rich (21–47 % ), and include plagioclase, pyroxene, biotite, amphibole, and oxides as the main phenocryst phases. Such differences in mineralogy and textures (i.e., vesicularity and crystallinity) suggest that PD and LD were likely sourced from different magmatic sources with different eruption styles (explosive and effusive styles, respectively). We have suggested that civilization settlements near PD are facing major threats from explosive magmatic, phreatomagmatic, and phreatic eruptions that could produce significant fallouts, ballistic materials, and highly destructive pyroclastic density currents. LDs pose a threat in the form of effusive magmatic eruptions such as lava flows and/or domes.